2019
DOI: 10.1111/ijfs.14415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of carrot fibre powder addition on rheological, microstructure and sensory characteristics of stirred‐type yogurt

Abstract: The incorporation of 1% (E1) and 2% (E2) of the carrot fibre powder obtained from carrot discards to yogurts was studied. The effect of the fibre addition on the physicochemical parameters, waterholding capacity (WHC), microbial counts, rheological, microstructure and sensory characteristics of yogurts was studied in comparison with control yogurt without fibre addition (C). Titratable acidity, global composition and microbial counts showed a similar trend among yogurts. Fibre particles seemed to change the or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This phenomenon demonstrates that BSGPs resulted in the yogurt having increased gel formation, which could be beneficial for the textural properties as well as for the consistency and for reducing syneresis. Different shear stress trends in yogurt have been reported previously and were found to be dependent on the ingredients that had been added as well as the treatments ( Azari-Anpar et al, 2021 ; Körzendörfer et al, 2019 ; Vénica et al, 2020 ), which were shown to be related to flow behavior-related properties, microstructural properties, and syneresis.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…This phenomenon demonstrates that BSGPs resulted in the yogurt having increased gel formation, which could be beneficial for the textural properties as well as for the consistency and for reducing syneresis. Different shear stress trends in yogurt have been reported previously and were found to be dependent on the ingredients that had been added as well as the treatments ( Azari-Anpar et al, 2021 ; Körzendörfer et al, 2019 ; Vénica et al, 2020 ), which were shown to be related to flow behavior-related properties, microstructural properties, and syneresis.…”
Section: Resultsmentioning
confidence: 55%
“…The shear stress of the YC increased due to the increase in the shear rate, while the yogurt prepared with the YP had the most stable shear stress. Shear stress represents the energy required to damage the structure of the yogurt matrix ( Vénica et al, 2020 ), thus showing the strength of the matrix. Because of this, the addition of BSGP-C might have induced gel formation faster than BSGP-P and BSGP-PF.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of yogurt samples included the following sensory attributes: appearance, color, texture, acidity, taste and overall acceptability. The scale used is the 9-point Hedonic scale, where 1 means dislike extremely, 5 means neither dislike nor like, and 9 means like extremely ( Vénica et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies published in the works of various scientists claim that during the fermentation process, lactic acid produced by bacterial cultures causes a reduction in pH, from an initial value of about 6.0 -6.5 to a final pH of 4.0 -4.6 (Mediza Romero et al, 2021;Vénica et al, 2020). As soon as the pH of the product has reached the value within the limits of 4.0-4.6, the fermentation process is stopped by placing the yoghurt in the cold.…”
Section: The Evolution Of Ph During Fermentationmentioning
confidence: 99%